1979
DOI: 10.3168/jds.s0022-0302(79)83371-8
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Ascorbic Acid (Vitamin C) in Iron-Supplemented Cows’ Milk

Abstract: The fate of [6-carbon-14] ascorbic acid in iron-supplemented and unsupplemented raw milk was studied by anion-exchange chromatography, which permitted quantitative analysis of the conversion of ascorbate to dehydroascorbate and diketogulonate as a function of time. Iron catalyzed an increase in the rate of autoxidation of ascorbate to dehydroascorbate but did not alter the equilibrium concentrations of ascorbate, dehydroascorbate, and diketogulonate. The conversion of ascorbate to dehydroascorbate and of dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Iron that was bound to the casein micelles remained with individual caseins even after dissociation of the micelle and ion-exchange chromatography on DEAE-cellulose in urea buffers (Figure 5). Our chromatographic system, using urea for dissociation and bisulfite for anaerobiasis (Hegenauer et al, 1979c)) was patterned after the urea-mercaptoethanol system described by Thompson (1966). Thiol reducíants like mercaptoethanol could not be used, however, because they reduced iron(III) and removed it from the caseins by chelation of iron(II).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron that was bound to the casein micelles remained with individual caseins even after dissociation of the micelle and ion-exchange chromatography on DEAE-cellulose in urea buffers (Figure 5). Our chromatographic system, using urea for dissociation and bisulfite for anaerobiasis (Hegenauer et al, 1979c)) was patterned after the urea-mercaptoethanol system described by Thompson (1966). Thiol reducíants like mercaptoethanol could not be used, however, because they reduced iron(III) and removed it from the caseins by chelation of iron(II).…”
Section: Resultsmentioning
confidence: 99%
“…Precipitated caseins were washed once by suspension/centrifugation with 0.5 M sodium acetate buffer (pH 4.60) and redissolved in 10 mL of urea-bisulfite buffer [5 M urea (deionized with mixed-bed resin)/5 mM NaHS03/5 mM Na^SCL, pH 7.12], and dialyzed under nitrogen for 24 h against 1 L of urea-bisulfite buffer in the cold. The dialyzed sample was applied to a column (1.5 X 25 cm) of DEAE-cellulose (Whatman "DE-52") previously equilibrated with urea-bisulfite buffer (Hegenauer et al, 1979c). A small amount of unadsorbed protein was removed by washing the column with about 100 mL of buffer, and caseins were eluted with a linear gradient (Hegenauer et al, 1965) formed between 250 mL of urea-bisulfite buffer (starting) and 250 mL of 0.3 M NaCl in urea-bisulfite buffer (limiting).…”
Section: Methodsmentioning
confidence: 99%
“…Vitamin C Total vitamin C of raw milk varied from 3.7 to 6.4 mg/lOO mL; average 5.0 mg/lOO mL, because of the great instability of ascorbic acid and its derivatives (Hegenauer et al, 1979). Immediately after pasteurization, the vitamin C retentions were as follows: HTST and Flash pasteurization reduced the vitamin C content by an average of 5 to 10%; HTST overpasteurization caused a 25% loss, and LTLT, 40%.…”
Section: Vitamin Bmentioning
confidence: 99%
“…In contrast, when milk was packed under air, additional O2 from head space or from the environment maintained the 0, content in the milk, thus keeping the rate of vitamin oxidation at a higher level . It has also been observed that the vitamin destruction could be further enhanced in the presence of heavy metals such as copper (Hegenauer et al, 1979).…”
Section: Dissolved O2mentioning
confidence: 99%
“…The corrosion rate of many metals in aqueous solutions can be dramatically increased by the addition of certain organic compounds to the solution, and ascorbic acid is one such compound (Massini, 1975). Since ferric ions catalyze the oxidation of ascorbic acid to dehydroascorbic acid in an autocatalytic reaction (Taqui-Khan and Martell, 1967; Sattar et al, 1977;Hegenauer et al, 1979), the corrosion of iron in ascorbic acid solutions may produce concentrations of ferric ions sufficient to catalyze the oxidation of ascorbic acid. This research project was designed to test this hypothesis and to determine the effect of ascorbic acid concentration on the corrosion rate of iron in an aerobic system.…”
mentioning
confidence: 99%